2010
DOI: 10.1253/circj.cj-10-0422
|View full text |Cite
|
Sign up to set email alerts
|

Fluffy Luminal Surface of the Non-Stenotic Culprit Coronary Artery in Patients With Acute Coronary Syndrome - An Angioscopic Study -

Abstract: Background: Approximately 15% of acute coronary syndrome (ACS) cases have no significant coronary stenosis. Mechanisms underlying the attacks are, however, unknown. Methods and Results:The clinical study had 254 patients with ACS; 38 patients (31 females and 7 males; aged 51.0±8.0 years) had no significant coronary stenosis on angiography. They underwent a dye-staining angioscopy of the suspected culprit coronary artery using Evans blue, which selectively stains fibrin and damaged endothelial cells. A fluffy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…14,15 Histological examinations in animals and patients revealed that this dye stains fibrin and damaged endothelial cells but not blood corpuscles. 10,[11][12][13] Discrimination of endothelial flap and globular thrombus was made according to the criteria described in the guidelines. 10 After observation by conventional angioscopy, 1 mL of 2.5% EB solution was injected during balloon inflation into the artery through the flush channel of the angioscope to stain the thrombus, and then the balloon was deflated for blood flow restoration.…”
Section: Dye-staining Angioscopy Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Histological examinations in animals and patients revealed that this dye stains fibrin and damaged endothelial cells but not blood corpuscles. 10,[11][12][13] Discrimination of endothelial flap and globular thrombus was made according to the criteria described in the guidelines. 10 After observation by conventional angioscopy, 1 mL of 2.5% EB solution was injected during balloon inflation into the artery through the flush channel of the angioscope to stain the thrombus, and then the balloon was deflated for blood flow restoration.…”
Section: Dye-staining Angioscopy Proceduresmentioning
confidence: 99%
“…9,10 The present dyestaining angioscopic study was therefore performed to visualize fibrin in coronary thrombus and to examine the roles of fibrin in the genesis of ACS.…”
mentioning
confidence: 99%
“…Histologically, the fluffy surface was composed of fibrin threads arising from the damaged ECs and adhered together by platelets. Therefore, it is proposed that a coronary segment with a fluffy or frosted glass-like surface is the site of surface disruption, and resultant thrombosis and the changes are related to residual fibrin and platelets after autolysis of the thrombus [17]. …”
Section: Dye-staining Coronary Asmentioning
confidence: 99%
“…The same mechanisms may participate in patients with ACS without significant coronary stenosis, or without demonstrable plaque disruption. However, the genesis of endothelial damage remains to be elucidated [29]. Extensive endothelial cell apoptosis induced through catecholamine-␤-adrenoceptorcaspase pathway [30] may play a role in this phenomenon.…”
Section: Acute Coronary Syndromes Without Obvious Coronary Plaque Disruptionmentioning
confidence: 99%